(untitled) (Research, Society and Development, 2020)
Introduction: head and neck squamous cell carcinoma (HNSCC) is a type of malignant tumor quite common in the world and has worrying survival rates. Therefore, establishing biomarkers, such as SOX2, which is associated with the proliferation of cancer stem cells (CTCs), is important for early detection of the disease, as well as determining the prognosis, which assists in the treatment. Purpose: analyze the performance of SOX2 as a prognostic predictor for HNSCC. Materials and Methods: this is an systematic literature review realized in BVS, PUBMED, Web of Science and SCOPUS databases, based on the strategy “SOX2 AND (oral squamous cell carcinoma OR head and neck squamous cell carcinoma) AND (prognosis OR aggressiveness)”. The final sample consisted of 19 articles. Results: survival data showed divergence between the studies: 10 studies concluded that the greater expression of SOX2 is associated with a good prognosis, while 8 concluded the opposite. 1 article did not show a relationship between the two factors. Data on the occurrence of metastases, mesenchymal epithelial transition, tumor proliferation and invasion were analyzed, resulting in radiotherapy, grade, differentiation and size of the tumor, with divergent notes between studies. Conclusion: the clinical findings point to relationships between SOX2 and the CECP, however, not conclusively. Thus, the literature does not support the use of SOX2 as a prognostic predictor, reinforcing the need to elucidate mechanisms and molecular pathways through which SOX2 influences the progression of cancer.